Live Broadcasting of High Definition Audiovisual Content Using HDTV over Broadband IP Networks. (5th January 2009) - Vegiris, C. E.; Avdelidis, K. A.; Dimoulas, C. A.; Papanikolaou, G. V.
Abstract : The current paper focuses on validating an implementation of a state-of-the art audiovisual (AV) technologies setup for live broadcasting of cultural shows, via broadband Internet. The main objective of the work was to study, configure, and setup dedicated audio-video equipment for the processes of capturing, processing, and transmission of extended resolution and high fidelity AV content in order to increase realism and achieve maximum audience sensation. Internet2 and GEANT broadband telecommunication networks were selected as the most applicable technology to deliver such traffic workloads. Validation procedures were conducted in combination with metric-based quality of service (QoS) and quality of experience (QoE) evaluation experiments for the quantification and the perceptual interpretation of the quality achieved during content reproduction. The implemented system was successfully applied in real-world applications, such as the transmission of cultural events from Thessaloniki Concert Hall throughout Greece as well as the reproduction of Philadelphia Orchestra performances (USA) via Internet2 and GEANT backbones.